Suitability of the litchi erineum mite, Aceria litchii (Keifer), as prey for the mite Phytoseius intermedius Evans & MacFarlane (Acari: Eriophyidae, Phytoseiidae) - Azevedo, Leticia Henrique [UNESP]; Castilho, Raphael de Campos [UNESP]; Moraes, Gilberto Jose de (Systematic & Applied Acarology Soc London, Natural History Museum, 2016)
Litchi (Litchi chinensis Sonn.; Sapindaceae) is a plant native to Southeast Asia, where it is mostly cultivated. This crop has been severely damaged in Australia, Brazil, China, Hawaii, India and Pakistan by the litchi erineum mite, Aceria litchii (Keifer) (Eriophyidae), which attacks mainly leaves but also flowers and fruits. Phytoseius intermedius Evans & McFarlane is one of the phytoseiid mites most commonly found in association with this pest in Brazil. The objectives of this study were to: a) to compare the predation and oviposition rates of P. intermedius when fed A. litchii with the same rates when the predator was fed other food sources [the eriophyid Aculops lycopersici Tryon, the spider mite Tetranychus urticae Koch and pollen of Typha domingensis (Pers.)]; b) to evaluate the life history parameters of P. intermedius fed A. litchii. The results indicated that A. litchii is a suitable food source for nymphs and adults P. intermedius. The combined immature stages (egg-adult) lasted 6.0 +/- 0.1 days, with fecundity recorded at 25.4 +/- 1.5 eggs, and a corresponding average oviposition rate of 1.2 +/- 0.1 eggs per day. The intrinsic rate of increase (r(m)) was 0.229 female/female/day. All field collected specimens and laboratory reared progeny of P. intermedius consisted of females, indicating that it most likely reproduces by thelytokous parthenogenesis.
Keywords: biological control; predator; life cycle; litchi